Web-based assessment of information systems services quality in Malaysian government agencies - 178018 M. Poobalan M. Masilamani (Skudai : Universiti Teknologi Malaysia, 2005)
Thesis (Sarjana Sains (Sains Komputer)) - Universiti Teknologi Malaysia, 2005